Integrative design and fabrication methodology for bio-inspired folding mechanisms for architectural applications. (April 2021) - Körner, Axel; Born, Larissa; Bucklin, Oliver; Suzuki, Seiichi; Vasey, Lauren; Gresser, Götz T.; Menges, Achim; Knippers, Jan
Abstract: Adaptive shading devices are of special interest in the context of global need for reducing greenhouse gas emissions. To reduce mechanical complexity of kinetic architectural applications, the investigation of bio-inspired compliant mechanisms has proven to be a promising approach. Thus, a coherent integrative design framework for bio-inspired kinetic folding mechanisms has been developed. This includes the abstraction process of biological principles, such as kinematic behaviours, actuation, as well as materialisation principles. A computational design and simulation model is built to analyse the kinematic and kinetic behaviour of the abstracted biological principles under consideration of specific materialisation and fabrication parameters and constraints. The design and simulation model builds the basis for an automated fabrication process, as well as for interaction and active control of the physical application. The development of the ITECH Research Demonstrator 2018–19, ​ a large-scale compliant folding mechanism, inspired by the folding behaviour ladybug wings ( Coleptera coccinellidae ), serves as a case study of the developed process. The folding motion of the demonstrator is facilitated by distinct elastic hinge-zones with integrated pneumatic actuators. Graphical abstract: Highlights: Integrative workflow for design, simulation, and fabrication of folding mechanisms. Simulating asymmetric actuation of folding patterns using constraint based dynamics. Kinetic simulation of flexible hinge zones and integrated pneumatic actuators. Interactive interaction scenarios with physical demonstrator. Development of the physical demonstrator to evaluate developed integrative process.